Perforation of duodeno-jejunal junction in an 8-month-old infant: A management challenge to a general surgeon. - Lee, Limi; Dayang Anita, A.A.; Liew, Ngoh Chin; N., M. Safian (Malaysian Medical Association, 2011)
We report a case of perforation over duodeno-jejunal junction (DJ) in a healthy 8-month-old baby. The difficulty in diagnosis, management dilemma and probable etiology is discussed.